Patterns of Social Interaction in Post-Covid-19 Offline Learning in The Sociology Education Study Program Unima - Veronike E. T Salem; Muhamad Fajar Hidayat; Yulian Hermanus Wenno; Romi Mesra (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
This study specifically wants to see patterns of interaction between students and lecturers after the Covid-19 pandemic has subsided. The study employs a qualitative method. Researchers used data collection methods, namely observation and interviews. Analyzing data in qualitative research is in the form of data reduction, data presentation, and drawing conclusions. The results of the study are as follows: 1) lecturers must remind students of the values ​​and norms that must be adhered to in interactions, 2) there is a cultural commotion between students, 3) adjustment of media and interaction tools between lecturers and students, 4) there are dynamics of social relations between students and between lecturers and students, 5) social interaction can be done anywhere.